Phytolith assemblages and systematic associations in grassland species of the south-eastern Pampean Plains, Argentina - Fernández Honaine, Mariana (2006)
• Background and Aims: Phytolith descriptions of South American plant species are scarce. This knowledge is crucial for the interpretation of the fossil phytolith record of a region. In this study phytolith assemblages and systematic relationships of the main grasses and Asteraceae species of Paspalum quadrifarium grassland are described. • Methods: Phytoliths from leaves of Poaceae and Asteraceae species were extracted by using a calcination technique. For each species, 350-400 phytoliths were counted and the relative frequency of each morphotype was calculated. Phytolith assemblages were subject to principal components analysis (PCA) and cluster analysis (Morisita index). • Key Results: PCA and cluster analysis showed family (Poaceae vs. Asteraceae) and subfamily (within Poaceae) differentiation. Exceptions to general trends described for other species were detected. Floristic variants of Paspalum quadrifarium grassland can be separated by their phytolith assemblages. • Conclusions: The study provides a reference collection of phytolith assemblages of the main Poaceae and Asteraceae species of Paspalum quadrifarium grassland and describes some phytolith morphotypes/systematic relationships useful for the analysis of fossil phytolith assemblages of the Pampean region.